Insight into trifluoromethylation – experimental electron density for Togni reagent I12. Issue 60 (5th October 2018) - Wang, R.; Kalf, I.; Englert, U.
Abstract : The experimentally observed electron density for the "Togni reagent" explains the interaction of the hypervalent iodine atom with a nucleophile. Abstract : 3, 3-Dimethyl-1-(trifluoromethyl)-1, 3-dihydro-1-λ3, 2-benziodoxole represents a popular reagent for trifluoromethylation. The σ hole on the hypervalent iodine atom in this "Togni reagent" is crucial for adduct formation between the reagent and a nucleophilic substrate. The electronic situation may be probed by high resolution X-ray diffraction: the experimental charge density thus derived shows that the short intermolecular contact of 3.0 Å between the iodine and a neighbouring oxygen atom is associated with a local charge depletion on the heavy halogen in the direction of the nucleophile and visible polarization of the O valence shell towards the iodine atom. In agreement with the expectation for λ3-iodanes, the intermolecular O⋯I–Caryl halogen bond deviates significantly from linearity.